Deformation and energy damage characteristics of granite-concrete composite under uniaxial compression - Qingwen Li; Shuhan Gu; Hanjing Li; Wenxia Li; Mengjiao Xu; Yiwei Liu (PLoS ONE, 2025)
To investigate the influence of the fractured rock-concrete interface on the mechanical response of the rock mass and engineering, the mechanical properties and energy evolution of granite-concrete composite specimens with 16 different fracture inclinations were examined through uniaxial compression particle flow simulation. The results show that when the relative area is constant, the larger the fracture dip angle is, the compressive strength of the composite body presents a similar “peak” type change; the dip angle appears to have the maximum value at 60 o and 90o and the minimum value at 0 o and 30 o, while the peak elastic modulus presents a “waterfall” type change, and the maximum value appears at 90o. The crack types were classified as shear cracks, tensile cracks, secondary shear cracks, secondary tensile cracks, shear-dominated mixed cracks, and tension-dominated mixed cracks. From the crack distribution, it was found that the root cause of crack initiation and propagation was affected by the crack inclination angle. The damage degree increased gradually with the increase of crack inclination angle. When the crack inclination angle was constant, the deterioration degree of the specimen weakened with the increase of relative area s. The elastic energy consumption ratio increases with the shaft deformation, first rapidly and steeply decreasing to the steady inflection point, then slowly increasing to the rapid and steep increase, showing a “fishhook” shape. When the strength failure occurs, the growth speed increases suddenly, and the elastic energy consumption ratio increases suddenly after the K peak. This phenomenon can be used as the basis for the occurrence of strength failure and can be used as a qualitative judgment of strength failure.